Sinodalità e primato nel pontificato di papa Francesco - Faggioli, Massimo (JoMaCC, 2024)
Pope Francis has undoubtedly not only received into the papal magisterium, but also made the recovery of ecclesial synodality as an evolution of the ecclesiology of Vatican II a central part of the agenda of his pontificate. At the same time, this recovery of synodality goes together, in the theology and practice of government of Pope Francis, with a notion and exercise of a strong papal primacy, and occurs in a moment of redefinition, in practice, of the criteria of the unity of Catholicism as global Catholicism, in a communion of churches that are increasingly different from each other. The relationship between synodality and primacy, as it unfolded in the first eleven years of Francis’ pontificate, leaves many questions open on the outcomes of the ‘synodal process’ (2021‑24) in the medium and long term, as well as on the forms that the exercise of the papal primacy will assume.